2010
DOI: 10.1029/2009jd012518
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of mesoscale convective systems at the land‐ocean transition in Senegal during NASA African Monsoon Multidisciplinary Analyses 2006

Abstract: [1] In this study we investigate the development of a mesoscale convective system (MCS) as it moved from West Africa to the Atlantic Ocean on 31 August 2006. We document surface and atmospheric conditions preceding and following the MCS, particularly near the coast. These analyses are used to evaluate how thermodynamic and microphysical gradients influence storms as they move from continental to maritime environments. To achieve these goals, we employ observations from NASA African Monsoon Multidisciplinary A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 118 publications
(108 reference statements)
1
18
0
Order By: Relevance
“…More vertically developed storms display a greater propensity for mixed-phase processes (DeMott and Rutledge, 1998;Nesbitt et al, 2006), enhancing the stratiform region and leading to larger precipitation contribution over the course of the study from deep convection observed over the continent (Figure 9(e)-(f)). DeLonge et al (2010) showed that MCSs transitioning from land to ocean exhibit signs of disorganization, resulting in less intense convective characteristics over the ocean. Figure 4 indicates that storms at the coast experienced a higher likelihood to enter a region with higher CAPE, which would theoretically produce stronger updrafts and significant lofting of precipitationsized particles.…”
Section: Precipitation Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…More vertically developed storms display a greater propensity for mixed-phase processes (DeMott and Rutledge, 1998;Nesbitt et al, 2006), enhancing the stratiform region and leading to larger precipitation contribution over the course of the study from deep convection observed over the continent (Figure 9(e)-(f)). DeLonge et al (2010) showed that MCSs transitioning from land to ocean exhibit signs of disorganization, resulting in less intense convective characteristics over the ocean. Figure 4 indicates that storms at the coast experienced a higher likelihood to enter a region with higher CAPE, which would theoretically produce stronger updrafts and significant lofting of precipitationsized particles.…”
Section: Precipitation Characteristicsmentioning
confidence: 99%
“…Land-to-ocean transitioning MCSs (coastal site) have been shown to diminish in strength (e.g. DeLonge et al, 2010) due to less favourable thermodynamic (e.g. lower specific humidity) and dynamic (e.g.…”
Section: Convective Characteristics and Easterly Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…This instability leads to the formation and maintenance of (often intense) MCSs (Aspliden et al, 1976;Payne and McGarry, 1977;Houze and Betts, 1981;Barnes and Sieckman, 1984;Rowell and Milford, 1993;Hodges and Thorncroft, 1997;Mohr and Thorncroft, 2006;Nicholls and Mohr, 2010). These westward-moving systems generally exhibit a linear (squall line) morphology over the continent (Hamilton et al, 1945;Eldridge, 1957;Bolton, 1984), a non-squall (amorphous) morphology over the eastern Atlantic Houze, 2003, 2006;Fuentes et al, 2008), and a transition stage upon exiting the coast (Sall and Sauvageot, 2005;DeLonge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the summer of 2006, the African Monsoon Multidisciplinary Analysis (AMMA) international field campaign and NASA-AMMA (NAMMA) collaborated to provide an observation network of various platforms stretching from Nigeria to the Cape Verde Islands [30,31]. Several studies have used the NAMMA data to examine the AEWs and MCSs moving off the African coast (e.g., [32][33][34][35]). In addition, one of the three main goals of AMMA-NAMMA was to determine a relationship between AEWs and MCSs that could provide insight into TC genesis.…”
Section: Introductionmentioning
confidence: 99%